Pengaruh Tugas Account Representative (AR) Terhadap Kepatuhan Wajib Pajak Di KPP Pratama Mataram Timur - Herawati Khotmi (Fakultas Ekonomi Universitas Islam Al-Azhar, 2019)
This research aims to determine the effects of AR (Account Representative) duty on tax compliance. The dependent variable in this study is taxpayer compliance. The independent variables in this study are service, consultation, exploration of potential and supervision. This is Associative Reasearch wich was conducted in Pratama Tax Office, East Mataram. In this reasearch, questionnaire was used to collect the data. The population in this study are 6,748 and Slovin formula was applied as the sampling technique with 99 questionnaires and 75 questionnaires returned. Based on the results of data analysis using the T test, it shows that the consultation results and potential exploration have no effect on taxpayer compliance. Whereas supervision and service have an effect on taxpayer compliance. F test results show that the consultation results, potential exploration, supervision and simultaneously or jointly service have an effect on taxpayer compliance. Based on results of this study, the researcher suggest that in carrying out the AR duty, it is better to increase consultation and explore potentials. Suggestion for the next researchers is considering to multiply the research sample and add variables such as mentoring and education.